2021
DOI: 10.1111/ijd.15846
|View full text |Cite
|
Sign up to set email alerts
|

Generalized ulcerative cutaneous sarcoidosis: an unusual presentation of the disease

Abstract: risk of graft necrosis from the limited vascular support and the inability to fill deeper defects, as subcutaneous fat is usually trimmed from the graft to enhance survival. 2,3 Additional possible complications include pin-cushioning, persistent dyschromia, and graft failure secondary to skin-edge tension associated with primary closure of the adjacent donor site. 2,3 In patients who prefer to avoid more involved surgical approaches, a local Burow's graft provides a simple, singlestage, single-site reconst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…A previous review (12) of 147 patients with cutaneous sarcoidosis found ulceration in 4.8% of patients, which is consistent with Powell's study (13). We reviewed 17 cases with full text from the English-language literature based on a PubMed search using the terms ulcerative sarcoidosis and case report for the last 20 years (13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28). They are presented in Table 3.…”
Section: Discussionmentioning
confidence: 99%
“…A previous review (12) of 147 patients with cutaneous sarcoidosis found ulceration in 4.8% of patients, which is consistent with Powell's study (13). We reviewed 17 cases with full text from the English-language literature based on a PubMed search using the terms ulcerative sarcoidosis and case report for the last 20 years (13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28). They are presented in Table 3.…”
Section: Discussionmentioning
confidence: 99%